Pengaruh Edukasi Kesehatan Tentang HIV/AIDS Terhadap Tingkat Pengetahuan Dan Stigma Remaja Pada HIV/AIDS - Arisah, Arisah; Hariyanti, Reni; Riya, Rosa; Lubis, Sunarti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
HIV/AIDS is a group of retroviruses that cause a decline in the sufferer's immune system, making them susceptible to various types of diseases. HIV/AIDS stigma often causes public rejection of people living with HIV/AIDS (PLWHA) because it is part of the cognitive component of a person or group of people who assess PLWHA negatively, therefore health education is needed so that knowledge increases and HIV/AIDS can be detected. This study aims to determine the effect of health education about HIV/AIDS on the level of knowledge and stigma of adolescents about HIV/AIDS at SMPN 18 Tanjung Jabung Timur. This type of research is a quasi-experiment. The population of this study were students at SMPN 18 Tanjung Jabung Timur. Sampling was taken using proportional random sampling and a sample size of 58 students was obtained. The data in this research are primary and secondary data. Data analysis used the Wilcoxon Signed Rank Test which had previously been tested for normality. There is a difference in the level of knowledge and stigma between the pretest and posttest scores (p value = 0.0000.05), so it can be concluded that there is an influence of health education on the level of knowledge and stigma of adolescents regarding HIV/AIDS.